Rupture of the Prepubic Tendon in a Quadruplet Pregnant Romanov Ewe - Yilmaz, Ö; Biçici, Ö; Karakaya-Bilen, E (Journal of the Hellenic Veterinary Medical Society, 2023)
A case of prepubic tendon rupture in a Romanov ewe in which four live lambs were removed by cesarean section is presented. A three-year-old ewe, on the 142±3 days of the second gestation was brought to the Siirt University Animal Health Application and Research Center with a sudden downward expansion of the abdomen during the last one day. When ewe was examined reluctance to locomotion, mild depression, tachycardia, tachypnea and abdominal peculiar enlargement on the left side more than right side were noticed. Because of this case was detected early the general condition was not so bad and clinical examination revealed that swelling was non-painful and non-edematous. Ultrasonography was performed to detect viability of the fetuses, and to eliminate possibility of hernia of the abdominal muscles. Based on anamnesis, abdominal palpation, and clinical examination, this case was diagnosed with prepubic tendon rupture. The prognosis of saving the lives of ewe and fetuses depends on successfully handling all aspects of the case in the last period of pregnancy. Although it is not possible to repair the abdominal integrity surgically in cases of prepubic tendon rupture in the ewe, a planned cesarean operation is indicated to increase the survival rates of both ewe and lambs.